Preliminary study: effect of 95% ethanol extract of senna auriculata flower on streptozotocin- induced diabetes rats. - Ali, Niswathul Haania Zain (Universiti Sains Malaysia, 2009)
Diabetes mellitus is a disease of lifestyle which was observed to be more common in the upper classes where they consume more unhealthy food and for this reason diabetes mellitus is called rich man's disease and it has a vast impact on global burden of mortality. Data published in journal showed that both of the aqueous and ethanol extract of Senna auriculata (SA), have strong anti-hyperglycemic effect in the short term to reduce blood glucose level in STZ- induced diabetic rats. The main objective of this study is to evaluate the effect of 95 % ethanol extract of Senna auriculata prepared via rotary evaporation method on streptozotocin (STZ) - induced diabetic male rats. In this study, Sprague Dawley male rats of body weighed 130-180 grams were selected and randomly assigned to 6 groups. The diabetic negative control rats were given orally carboxyl methyl cellulose (CMC) 2% as vehicle and positive control rats were given 15mg/kg metformin also orally. While the rats in treatment group were given 95 % ethanol extract of Senna auriculata via oral route at doses 50,100 and 200 mg/kg daily respectively for 25 days. The rats body weight, fasting blood glucose and physical changes were observed throughout the study period. At the end of the study period the blood glucose level were measured before the rats sacrificed after anesthetized. The rats' pancreas was taken for histological examination. The fasting blood glucose were not significantly different (p>0.005) in SA treated diabetic group compared to diabetic control group after treatment for 25 days with 95 % ethanol extract of SA. Based on the data produced it shows that 95 % ethanol extract of Senna auriculata flower have no anti-hyperglycemic effect on STZ- induced diabetic male rats.